The Political Role of Women in the City of Santri, Situbondo (Overview of Political Communication) - Nur Ainiyah (Islamic Studies Journal for Social Transformation, 2018)
This study aims to show how the role of women's political communication in the city of santri (a student in Islamic boarding school) in facing political power that is dominated by men in Situbondo. It becomes a development in women's political communication in a practical and scientific manner. The reality of the political climate in Situbondo is inseparable from the influence of the kyai as religious and cultural figures, so each of his political perceptions and views certainly has its own perspective and far from gender justice. Consequently, this affects the political space for female santri in Situbondo. In this research, building theoretical interconnections from building theoretical frameworks used such as political communication, gender analysis and phenomenology, related to the focus of research. With a qualitative-explorative research approach, several steps in the procedure of collecting observational data, interviews and documentation are applied consistently and continuously. The results of the research are firstly Santri woman has a political outlook with the benefit of minimizing conflict; secondly cultural barriers as a medium of political communication are effectively overcome by female santri. Besides, female santri tend to override political choices by preferring the political choices of the figures they envision for benefit purposes.